PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GAME TEBAK OPERASI MATEMATIKA YANG BERORIENTASI PADA KEMAMPUAN BERPIKIR KRITIS - Nur Hasanah (STKIP PGRI Situbondo, 2023)
This study aims to develop game learning media with the aim of making students enjoy learning mathematics and reducing the level of students' thinking that mathematics is difficult and not fun. In addition to these things, this research also develops oriented math games so that students can think critically in every problem. Study this use method study and development of the proposed 4D model by Thiagarajan which consists of 4 stages namely : (1) define or definition ; (2) designs or planning ; (3) develop or development and (4) disseminate or deployment . Beginning with planning in the selection of media to carry out developments that are in accordance with what is needed for learning mathematics. This research produces math game-based learning media that is suitable for use as a learning medium with the aim of students' critical thinking skills, namely valid and feasible to use as learning media and the results obtained implementation device development learning on class X shows an average increase critical thinking ability . Result _ analysis Post test show Skills think critical student or as much 80 % students complete and 20 % students no complete